Assembly and Analysis of the Complete Mitochondrial Genome of Capsella bursa-pastoris - Denis O. Omelchenko; Maxim S. Makarenko; Artem S. Kasianov; Mikhail I. Schelkunov; Maria D. Logacheva; Aleksey A. Penin (Plants, 2020)
Shepherd’s purse (Capsella bursa-pastoris) is a cosmopolitan annual weed and a promising model plant for studying allopolyploidization in the evolution of angiosperms. Though plant mitochondrial genomes are a valuable source of genetic information, they are hard to assemble. At present, only the complete mitogenome of C. rubella is available out of all species of the genus Capsella. In this work, we have assembled the complete mitogenome of C. bursa-pastoris using high-precision PacBio SMRT third-generation sequencing technology. It is 287,799 bp long and contains 32 protein-coding genes, 3 rRNAs, 25 tRNAs corresponding to 15 amino acids, and 8 open reading frames (ORFs) supported by RNAseq data. Though many repeat regions have been found, none of them is longer than 1 kbp, and the most frequent structural variant originated from these repeats is present in only 4% of the mitogenome copies. The mitochondrial DNA sequence of C. bursa-pastoris differs from C. rubella, but not from C. orientalis, by two long inversions, suggesting that C. orientalis could be its maternal progenitor species. In total, 377 C to U RNA editing sites have been detected. All genes except cox1 and atp8 contain RNA editing sites, and most of them lead to non-synonymous changes of amino acids. Most of the identified RNA editing sites are identical to corresponding RNA editing sites in A. thaliana.